Persepsi Masyarakat Lombok Terhadap Seksologi Dalam Lontar Resi Sembina Pada Masa Grahasta Asrama - I Made Agus Yudhiarsana; Ida Bagus Alit Arta Wiguna; Ni Made Arini (Jayapangus Press, 2021)
Understanding the meaning and sanctity of sex as a biological need that has the same position as the need to eat and drink leads humans to their nature to fulfill sexual needs. To find out the understanding of the Hindu community in Lombok about the philosophical value of the discourse of intercourse in the text of Lontar Resi Sembina. This study used a descriptive type of research with a qualitative approach. In this study, we dissect a literary source in the form of lontar, which will then be linked to data on public perceptions of the teachings in the text of Lontar Resi Sembina. (1) Public understanding of Hindu religious teachings, especially regarding tattwa or the philosophical meaning of intercourse in living the life of Grahasta Asrama or having a household in Pagesangan Village, is still shallow. (2) almost all people in Pagesangan Village do not have literary sources that discuss sexual intercourse or kama tattwa. (3) there is a discrepancy between the public's view of the importance of fulfilling sexual libido as one of the expressions of kama in life, with the fulfillment of sources of information, both primary in the form of lontar literature, books, and other socialization media as well as supporting information sources in the form of the existence of Hindu intellectuals in the dissemination of tattwa teachings contained in the text of Lontar Resi Sembina.